Partisan Selective Engagement: Evidence from Facebook - Marcel Garz; Jil Sörensen; Daniel F. Stone (Center for Economic Studies and ifo Institute (CESifo), 2019)
This study investigates the effects of variation in "congeniality" of news on Facebook user engagement (likes, shares, and comments). We compile an original data set of Facebook posts by 84 German news outlets on politicians that were investigated for criminal offenses from January 2012 to June 2017. We also construct an index of each outlet's media slant by comparing the language of the outlet with that of the main political parties, which allows us to measure the congeniality of the posts. We find evidence that users engaged with congenial posts more than with uncongenial ones, especially in terms of likes. The within-outlet, within-topic design allows us to infer that the greater engagement with congenial news is likely driven by psychological and social factors, rather than a desire for accurate or otherwise instrumental information.
Keywords: D83; D91; L82; 330; filter bubble; media bias; political immunity; social media; polarization